Effect of composition and sintering temperature on silica-nickel oxide foams by slurry method - Baharom, Syazwani (2017)
It has been a long-standing effort to create materials with low density but high strength. Foam materials are very light, but compared with bulk materials, their strength is quite low because of their random structures. Natural lightweight materials such as bone, is a cellular solid with optimized structure. The aim of this study is to fabricate silica-nickel oxide (SiO2-NiO) foams with 20 μm to 800 μm open pore size, 50% to 80% of porosity, good physical and mechanical properties. In this research, silica (SiO2) powder and nickel oxide (NiO) powder with different compositions of 2 wt.%, 4 wt.%, 6 wt.%, 8 wt.% and 10 wt.% were mixed together with binders which were polyethylene glycol (PEG) and carboxymethyl cellulose (CMC) to prepare slurry solution for impregnation of polyurethane (PU) sponge as the template. Silica-Nickel Oxide foams were fabricated by slurry method and sintered at 1000ºC, 1100ºC, 1200ºC and 1300ºC. Characterisation of SiO2-NiO foams included morphological analysis, porosity and density test, and compression test were done to determine the foam microstructure, apparent porosity, bulk density and compressive strength. The morphology of SiO2-NiO foam showed open pore with size ranging from 20 μm to 739 μm, interconnected cells by strut and close pore. The result of apparent porosity and bulk density of SiO2-NiO foams calculated according to Archimedes’ principle. The lowest result for apparent porosity obtained was 53.03% and the highest was 66.21%, while the lowest and highest value for bulk density were 0.89 g/cm3 and 1.22 g/cm3, respectively. The result for compressive strength of SiO2-NiO foam was within the range of 0.21 MPa to 1.86 MPa. The foam with good physical and mechanical properties obtained by 6 wt.% of SiO2-NiO foams sintered at 1300°C and will be used for further research in steam methane reforming application.